Healing effect of matico (Piper aduncum) and propolis in post-surgical wounds of canines - Puglla Masaco, Gabriela Alexandra; Rubio Arias, Pablo Giovanny (Anatomía Digital, 2022)
Objective: to compare the healing effect of matico and propolis in the treatment of post-surgical wounds. Methodology: an observational and comparative study was conducted on the healing effects through three treatments T1 (Matico); T2 (Propolis) and T3 (Saline-placebo solution), assigning each treatment to eight bitches (Canis lupus familiaris) that underwent a surgical process of octubrehysterectomy (OVH), at the "San Fernandos" Veterinary Clinic in the city of Loja -Ecuador. Results: it was shown that the matico and propolis ointment achieved better results in healing time and wound length reduction, and that, although there were differences between these and the control group, there were no statistically significant differences in the results. between the ointment of matico and propolis. In addition, a lower number of patients with inflammation, pain, scab, necrosis, and infection were found in the groups treated with matico and propolis during the 21 days of study, compared to the control group, all important macroscopic characteristics studied in the wounds of the diverse groups. Conclusions: matico and propolis are effective in the treatment of post-surgical wounds, with a reduction in healing time and scar size compared to the control group, which had a longer healing time and little reduction in s Objetivo: comparar el efecto cicatrizante del matico y propóleo en el tratamiento de heridas postquirúrgicas. Metodología: se realizó un estudio observacional y comparativo sobre los efectos cicatrizante mediante tres tratamientos T1 (Matico); T2 (Propóleo) y T3 (Solución salina-placebo), asignándose a cada tratamiento 8 perras (Canis lupus familiaris) que fueron sometidas a un proceso quirúrgico de ovariohisterectomía (OVH), en la Clínica Veterinaria “San Fernandos” en la ciudad de Loja-Ecuador. Resultados: se demostró que la pomada de matico y propóleo lograron mejores resultados en el tiempo de cicatrización y la reducción de largo de la herida, y que, si bien existieron diferencias entre estos y el grupo ...